Statistical measures of the association between two ordinal variables - Liptaková Erika (Matej Bel University, 2021)
Abstract Questionnaire surveys often deal with items by which we would like to identify possible associations. These items/variables can be measured on the basis of nominal, ordinal or interval scale. This paper provides an overview of statistical measures of association between two ordinal variables that are used most commonly. It also offers a display of the outputs from the SPSS program, in addition to the description of correlation coefficient calculations. DOI: https://doi.org/10.24040/sjss.2020.6.2.55-61